US – China Priorities in the 21st Century - Shah, Syed Nouman; Majeed, Gulshan; Arshad, Farooq (Pakistan Journal of Humanities and Social Sciences, 2022)
The paper evaluates the priorities of the US and China with regards to economic, geopolitical, military technology, and alliance formation. In the economic aspect, we will study China's BRI policy and USA's B3W counter project. The goal of both states in this regard is to dominate the international market. Both the countries are investing in Hyper Sonic technology to gain an upper hand in the Military expanse. The formation of alliances is another clever tactic in the name of establishing mutual security. China's relationship with the US arch-enemy Russia and the Chabahar Port and CPEC projects with Iran and Pakistan respectively appear to be an alarming situation for the US. To counter China's increasing advancement, the US formed QUAD and AUKUS with India, Japan, Australia, and the UK, along with the Reciprocal Access Agreement to limit the escalating approach of China. The blame game between the US and China regarding the COVID-19 pandemic also sparked many controversies. The increased threat perceptions and more crucial political elements between the two powers are dynamics of global hegemony. Analytical and Descriptive methods of research are applied in the paper.